Vibrio alginolyticus Triggers Inflammatory Response in Mouse Peritoneal Macrophages via Activation of NLRP3 Inflammasome - Wang, Jinxin; Ding, Qun; Yang, Qiankun; Fan, Hui; Yu, Guili; Liu, Feixue; Bello, Babatunde Kazeem; Zhang, Xiao; Zhang, Tianmeng; Dong, Jingquan; Liu, Gang; Zhao, Panpan (Frontiers in Cellular and Infection Microbiology, 2021)
Vibrio alginolyticus is a food-borne marine Vibrio that causes gastroenteritis, otitis media, otitis externa, and septicemia in humans. The pathogenic mechanisms of V. alginolyticus have previously been studied in aquaculture animals; however, the underlying mechanisms in mammals remain unknown. In this study, an in vitro model of mouse peritoneal macrophages infected with V. alginolyticus was established. qPCR results revealed that V. alginolyticus induced the transcription levels of various cytokines, including IL-1β, IL-12, IL-18, TNF-α, IL-17, IL-6, IFN-γ, and IL-10, and the secretion level of IL-1β is the most significant. Inhibition assays with Ac-YVAD-CHO (a caspase-1 inhibitor) and Z-VAD-FMK (a pan-caspase inhibitor) were conducted to determine whether caspase-1 or caspase-11 is involved in V. alginolyticus-triggered IL-1β secretion. Results showed that IL-1β secretion was partly inhibited by Ac-YVAD-CHO and absolutely blocked by Z-VAD-FMK. To explore the sensed pattern recognition receptors, several NLR family members and the AIM2 receptor were detected and many receptors were upregulated especially NLRP3. Moreover, the NLRP3 protein displayed a puncta-like surrounding cell nucleus, which signified that the NLRP3 inflammasome was activated in response to V. alginolyticus infection. Inhibition assays with glyburide and CA-074 methyl ester (K+ outflow inhibitor and cathepsin B inhibitor) blocked IL-1β secretion, which demonstrated the essential role of the NLRP3 inflammasome in inflammatory response. To better understand how V. alginolyticus affects IL-1β release, the NLRP3 inflammasome was detected with doses ranging from 0.1 to 10 MOIs and time periods ranging from 3 to 12 h. Results showed that V. alginolyticus-mediated NLRP3 inflammasome activation was in a time- and dose-dependent manner and IL-1β release peaked at MOI of 1 for 12 h. Most importantly, blocking the NLRP3 inflammasome with inhibitors and the use of NLRP3-/- and caspase-1/11-/- mice could attenuate pro-inflammatory cytokine secretion, such as IL-1β, IL-6, IL-12, and TNF-α. Taken together, our study first found that the NLRP3 inflammasome plays vital roles in V. alginolyticus triggered inflammatory response in mouse peritoneal macrophages. This may provide reference information for the development of potential anti-inflammatory treatments against V. alginolyticus infection.